Differences in Levodopa Response for Progressive and Non-Progressive Micrographia in Parkinson's Disease - Zham, Poonam; Poosapadi, Sridhar A.; Kempster, Peter; Raghav, Sanjay; Nagao, Kanae J.; Wong, Kitty; Kumar, Dinesh (Frontiers in Neurology, 2021)
Background: Micrographia, one element of the dysgraphia of Parkinson's disease (PD), may be classified according to the presence or absence of a decremental pattern. The decremental form, progressive micrographia, is an expression of the sequence effect seen generally in bradykinesia. Its responsiveness to levodopa has not been evaluated kinematically. Objectives: Aim of this study is to investigate the difference in levodopa response for progressive and non-progressive micrographia. Methods: Twenty-four PD patients and 24 age-matched repeatedly wrote the letter e on a computerized digital tablet. PD patients performed the task two times, in a defined off state and again after levodopa. Scripts were classified as progressive micrographia (PDPM) or non-progressive micrographia (PDNPM) depending on whether a 10% decrement was seen between the first and final characters of a line of lettering. Results: While levodopa produced a similar response on the MDS-UPDRS motor scale for the two groups, the effect on the two types of micrographia was different. While writing speed improved significantly in both groups after levodopa, the responses were over twofold greater for PDNPM. Moreover, the decremental features of PDPM–in size, speed, and pen-pressure—were largely unaltered by a levodopa dose. Conclusions: Progressive micrographia is less responsive to levodopa. Our findings agree with research showing that the sequence effect of bradykinesia is relatively resistant to medication. Yet we did not find a weaker overall levodopa motor benefit. Caution is needed in the interpretation of such micrographia measurements for estimating drug responses.